Cyclical lending standards: A structural analysis - Kaiji Chen; Patrick Higgins; Tao Zha (Federal Reserve Bank of Atlanta, 2020)
Lending standards are a direct measure of credit conditions. We use the micro data merged from three separate sources to construct this measure and document that an uncertain macroeconomic outlook, rather than banks' balance sheet positions, was an important reason that a majority of banks tightened bank lending standards during the Great Recession. Our extensive data analysis disciplines how we introduce credit frictions in the banking sector into a macroeconomic model. The model estimation reveals that an exogenous shock to credit supply drives cyclical lending standards and accounts for a significant portion of fluctuations in bank loans and aggregate output.
Keywords: E32; E44; G21; C51; C81; C82; 330; asymmetric credit allocation; endogenous regime switching; debt-to-GDP ratio; heavy GDP; heavy loans; real estate; land prices; GDP growth target; nonlinear effects